Solve for y -6y+26=-4(y-9)

Math
-6y+26=-4(y-9)
Simplify -4(y-9).
Tap for more steps…
Apply the distributive property.
-6y+26=-4y-4⋅-9
Multiply -4 by -9.
-6y+26=-4y+36
-6y+26=-4y+36
Move all terms containing y to the left side of the equation.
Tap for more steps…
Add 4y to both sides of the equation.
-6y+26+4y=36
Add -6y and 4y.
-2y+26=36
-2y+26=36
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 26 from both sides of the equation.
-2y=36-26
Subtract 26 from 36.
-2y=10
-2y=10
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2y=10 by -2.
-2y-2=10-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2y-2=10-2
Divide y by 1.
y=10-2
y=10-2
Divide 10 by -2.
y=-5
y=-5
Solve for y -6y+26=-4(y-9)
Scroll to top